Supping with the Devil: Belief and the Imaginary World of Multiple Myeloma Therapies Invented by the Institute for Clinical and Economic Review - Paul C Langley (INNOVATIONS in Pharmacy, 2021)
Previous commentaries in Innovations in Pharmacy and other peer reviewed journals have made the case that the analytical framework, if that is not too strong a term, to support pricing and access recommendations endorsed by the Institute for Clinical and Economic Review (ICER) fails to meet the standards of normal science. By any criteria the ICER analysis is best described as pseudoscience; it fails the demarcation test between biological evolution and intelligent design. Like intelligent design it has its believers; a meme for all seasons. ICER is fully aware of the fact that it fails these standards, yet perseveres. It justifies its cost-per-QALY framework by maintaining, through unsubstantiated assertions, that it meets standards for scientific credibility; it denies the possibility of negative values and utilities which undercut completely the construction of QALYs. This is nonsense: not only does the ICER framework fail those standards, to include axioms of fundamental measurement, but also a simple rule of logic in basing its models on assumptions. ICER dogmatic adherence to simulation modeling is evidence in its latest report on multiple myeloma. The report is a charade; but unfortunately not one that is rejected by Bristol-Myer Squibb, GlaxoSmithKline, Sanofi and Amgen. Their responses to the draft evidence report points to their acceptance of imaginary simulation constructs to drive pricing decisions. Whether this reflects their unqualified acceptance of the imaginary simulation modelling to create evidence or a failure to appreciate the standards of normal science is unclear. Certainly, in this case they fail to recognize the devastating impact of believing in the use of the EQ-5D-5L preferences to create imaginary or I-QALYs. The question raised in this commentary is whether the willingness to accept the ICER analytical framework reflects a belief in the role of creating evidence, ICER style, or a willingness to accept ICER imaginary conclusions as the easy way out in negotiating prices with insurers and other payers. Accepting ICER imaginary constructs is an analytical dead end that will stifle the discovery of new facts. The question is: so what?